PENGARUH MODIFIKASI PEMBELAJARAN DENGAN MEDIA KARDUS TERHADAP HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK (STUDI PADA SISWA KELAS VII SMP NEGERI 4 BOJONEGORO) - ADY PRATAMA, YUDHA (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract An abstranct Physical education is a process of education through physical activity and also a process of education to increase physical capabilities. To achieve the possible best  goal of motion activity, the new methods to support the achievement of the activity is needed. Modification of learning materials of  the long jump with a squat-style using cardboard media to enhance student learning outcomes is a way to develop learning with media. Nowdays in the long jump learning, physical education teachers are still using the method of  common standard learning, so in the result, the learning process is still substandard and there is no modification of learning method in these games, as well as the less of enrichment of the motion so that the students have less sense of fun and joy. In order to make students enjoy and interest to join the physical lesson, physical education teachers are expected to create kinds clever variation or modifications of learning, especially in the long jump squat style. Research target are students of SMP Negeri 4 Bojonegoro grade VII and number of samples taken 2 Class by 60 students who were divided into 2 groups: experimental group and control group, each group consists of 30 students . The method in this analysis using two differen samples of t test are , while the data retrieval process is done using the long jump test style squat with a jump distance assessment guidelines. The results of analysis of two differen sample (Paired Sample t Test), namely: the experimental group and control group obtained the value t count = 1,96905and the calculation of the table t (0.05; 29) = 1,699).because since-t count > t table-is 1,96905 > 1,699. In other word as the result, there is effect of the influence of learning modification with cardboard media to the study result of the long jump squat style class VII SMP Negeri 4 Bojonegoro.From the modification of cardboard media can infolve the students’ studying result as 11,38%. Keywords : modified the cardboard media, learning resultsquat style long jump.